En busca del origen del conocimiento: el dilema de la realidad - Raúl Omar Di Marco-Morales (Universidad del Magdalena, 2015)
This article shows that it is not rare to have as its primary objective reality of knowledge, which must focus on human progress through scientific research. Knowing and knowing something (dilemma resides in humans) is becoming a problem in their daily lives. Knowledge is an organism with life as it changes and is enriched with new experiences, so that can go from an initial state to a more complex and more efficient final state, thanks to the main features of the new scientific knowledge or interpretation on any issue. Every scientist has a different concept of truth, as explained knowledge in various forms and also defined scientific theory as a metaphor, considering that science is a knowledge of the unit, while the opinions are merely from the crowd.